Disonansi Naratif dalam Komunikasi Korporasi: (Studi Kasus Ketidaksesuaian Klaim Produk dan Realitas Teknis pada Brand Aqua) - Nadhif Akmaludin; Laili Zulfa (Konstitusi : Jurnal Hukum, Administrasi Publik, dan Ilmu Komunikasi, 2025)
This study aims to analyze the narrative dissonance in the corporate communication of the Aqua brand, especially in the context of the crisis of meaning that arises between claims of natural purity and technical findings related to the use of borewells in the production process. Using a qualitative approach through content and narrative analysis, the study integrates two main theoretical frameworks: the Narrative Paradigm (Fisher, 1984) and Image Repair Theory (Benoit, 1995). The analysis focused on how companies are building, maintaining, and renegotiating their corporate narrative amid public pressure and consumer expectations. The results show that the legitimacy crisis arises due to the symbolic mismatch between the narrative of "purity" communicated and the operational reality revealed to the public. This tension triggered a strategic response from the company in the form of public clarification, transparency of the production process, and repositioning of messages to restore consumer image and trust. This study confirms the importance of narrative coherence and reflexivity in corporate communications, especially in an era of digital openness that demands accountability and consistency between symbolic messages and tangible practices. These findings contribute to the study of crisis communication and brand image restoration strategies, as well as a reference for companies in designing ethical, transparent, and sustainable communication to maintain legitimacy and credibility in the eyes of the public.